Comparison of Open and Endoscopic Approach in Carpal Tunnel Release: A Systematic Review - Pramana, I Kadek Adi Surya; Putri, Ni Nyoman Nila Manta Ary (Jurnal Health Sains, 2025)
Carpal Tunnel Syndrome (CTS) is a musculoskeletal disorder caused by the compression of the median nerve, with an incidence of 1 to 3 cases per 1000 people annually and a prevalence of 50 per 1000 in the United States. The two main surgical treatments for CTS are open carpal tunnel release (OCTR) and endoscopic carpal tunnel release (ECTR). This study aims to compare the outcomes of ECTR and OCTR based on randomized controlled trials (RCTs). A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, focusing on RCTs published between 2013 and 2023. The outcomes analyzed included the Boston Carpal Tunnel Questionnaire Symptom Severity Scale (BCTQ-S), Boston Carpal Tunnel Questionnaire Functional Status Scale (BCTQ-F), VAS score, and postoperative complications. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidelines were used to assess the level of evidence. Seven studies, including 271 hands treated with ECTR and 285 hands treated with OCTR, were reviewed. The comparison results showed minimal differences in BCTQ-S (MD=0.06), BCTQ-F (MD=0.02), VAS (MD=0.03), and complications (ECTR vs OCTR = 5 vs 9). Both ECTR and OCTR produced similar results, with only slight differences observed. In conclusion, ECTR and OCTR offer comparable outcomes based on BCTQ-S, BCTQ-F, VAS score, and postoperative complications. Despite some differences, these findings should be interpreted cautiously and not considered conclusive.